2022
DOI: 10.1097/jom.0000000000002743
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Cardiometabolic Disease in Professional Firefighters

Abstract: Firefighters are at elevated risk for developing cardiometabolic disease. These data show that having a high level of cardiorespiratory fitness, and low waist circumference is associated with reduced blood markers of insulin resistance, inflammation and oxidative stress. These findings providing implications for reducing cardiometabolic disease risk among firefighters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Previous studies suggested that higher CRF has been associated with decreased number of metabolic abnormalities among firefighters ( 31 , 32 ). Especially, McAllister et al reported that firefighter’s cardiorespiratory fitness (CRF) was negatively associated with surrogate estimated of insulin resistance (HOMA-IR) ( 33 ) and lowest CRF levels (Metabolic equivalents; METs ≤ 10) was a higher prevalence of MetSyn compared to highest CRF level (METs > 14) in US firefighter ( 26 ). Collectively, increases in CRF might be needed to prevent and treat hypertension, dyslipidemia, dysglycemia, and abdominal obesity among US firefighters.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested that higher CRF has been associated with decreased number of metabolic abnormalities among firefighters ( 31 , 32 ). Especially, McAllister et al reported that firefighter’s cardiorespiratory fitness (CRF) was negatively associated with surrogate estimated of insulin resistance (HOMA-IR) ( 33 ) and lowest CRF levels (Metabolic equivalents; METs ≤ 10) was a higher prevalence of MetSyn compared to highest CRF level (METs > 14) in US firefighter ( 26 ). Collectively, increases in CRF might be needed to prevent and treat hypertension, dyslipidemia, dysglycemia, and abdominal obesity among US firefighters.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, about 75% of firefighters are classified as overweight or obese (≈75%) [32][33][34]. Obesity is associated with lower levels of cardiorespiratory fitness, as well as clusters of other cardiovascular disease risk factors [32][33][34][35][36]. Evidence indicates that firefighters engage in sedentary behaviors and poor dietary practices, which further exacerbates the risk of premature mortality due to cardiovascular disease [37].…”
Section: Physical Health Threat: Cardiovascular Diseasementioning
confidence: 99%
“…These clinical assessments are recommended as essential procedures to be included in fire department annual medical exams [47]. As such, greater CRF is associated with reduced blood pressure [48], reduced arterial stiffness [49], and less desirable levels of total cholesterol, triglycerides, low-density lipoprotein cholesterol, insulin resistance, C-reactive protein, and advanced oxidation protein products [35,36,[50][51][52]. In addition, higher CRF is associated with lower body mass index (BMI), waist circumference, and percent body fat [53][54][55].…”
Section: Physical Health Countermeasure: Clinical and Fitness Assessm...mentioning
confidence: 99%
“…Most scientific studies published in this area to date involving firefighters concern the importance of occupational stress and burnout [ 8 , 9 ], the prevalence of cardiovascular disease in this occupational group [ 4 , 10 , 11 , 12 , 13 , 14 ] and obesity [ 15 , 16 ]. In Poland, scientific research efforts with the participation of State Fire Service firefighters are also limited and mainly refer to the analysis of sleep disorders [ 17 ], post-traumatic stress and burnout [ 18 ], or the frequency of accidents during work [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%